Outbreaks of avian cholera in Hope Bay, Antarctica - Leotta, Gerardo Aníbal (2006)
During austral summers 1999–2000 and 2000–01, two outbreaks of avian cholera occurred in the Hope Bay area (63u249S, 56u599W), located on the tip of the Antarctic Peninsula. Eighty-six dead birds were found: five kelp gulls (Larus dominicanus), 36 skuas (Stercorarius sp.), and 45 Adelie penguins (Pygoscelis adeliae). The carcasses were studied using clinical, pathological, and microbiological criteria. Water samples from ponds where birds were settled and samples from 90 healthy birds also were analyzed during the second outbreak. Pasteurella multocida isolates were identified by biochemical tests, capsular type, somatic serotype, and susceptibility to nine antibiotics. Molecular subtyping was performed by ApaI and SmaI pulsedfield gel electrophoresis (PFGE) and enterobacterial repetitive intergenic consensus (ERICPCR). In February 2000, mortality in skuas was 16% and 2% in kelp gulls. In the 2000–01 breeding season, mortality in south polar skuas was 47%, 24% in brown skuas, 1.4% in kelp gulls, and 0.01% in Adelie penguins. All birds had lesions of avian cholera. In kelp gulls the presentation was chronic, whereas skuas and penguins suffered subacute and acute disease, respectively. Fiftyfive isolates recovered from dead birds and one from water were identified as P. multocida gallicida, type A:1. The strains presented a unique molecular pattern by PFGE and ERIC-PCR. A possible hypothesis to explain the origin of the outbreaks was that nonbreeder kelp gulls carried P. multocida gallicida to Hope Bay, and avian cholera was transmitted through water to skuas and penguins. This study reports avian cholera in new bird species, their potential role in the transmission of the disease, and the different responses of these species to the disease.